Application of High-Tech Solution for Memory Assessment in Patients With Disorders of Consciousness - Kujawa, Katarzyna; Żurek, Alina; Gorączko, Agata; Zurek, Grzegorz (Frontiers in Neurology, 2022)
Testing cognitive function in patients after severe brain injury is a major clinical challenge. In the absence of both verbal and motor communication, tests commonly used to assess cognitive function are completely or partially undoable for disorders of consciousness patients. The study involved 12 patients with varying degrees of impaired consciousness due to brain injury, with no verbal and motor communication. Memory was assessed in study participants using oculography. Memory tasks were presented in four categories. The total percentage of correctly completed tasks obtained across the group was 40.97%. The most difficult tasks included category C.4 with tasks involving working memory. Regardless of the subjects' level of consciousness, there was no statistically significant difference in the percentage of correct responses obtained in subgroups distinguished by CRS-R score. Eye tracking technology can be successfully used in the assessment of cognitive function, particularly when eye movements are the only channel of communication in individuals after brain injury. We suggest that the cognitive functions of people after brain injury should be further analyzed using eye tracking.